Do lugar do(s) mapa(s) na viagem e seu relato ou muito para além de um atlas oficial - Outeirinho, Maria de Fátima (2016)
In a study on travel writing, 'Olhares suíços sobre Portugal: de Reynold a Loetscher', Gonçalo Vilas-Boas notes that 'Os afectos assumem também uma importância crucial na construção que os viajantes fazem daquilo que percecionam, influenciando o modo e a atitude de observação' (2011: 160); and in "Olhares sobre a Patagónia', Vilas-Boas reminds that 'Cada viajante estabelece a sua cartografia pessoal, dentro de uma cartografia mais abrangente, mais global.' (2014: 46). In fact, always in relation to space, the other, the world, the graphic and linguistic representation, reflected in the design and in the drawing of a map, became cognitive instrument, point of departure or arrival for whosoever think his being in the world, having or not experienced a physical displacement. From Anaximander's world map to Mademoiselle de Scudéry Carte de Tendre, to even more contemporary concept maps, the process and the mapping dynamics give to see or refigure a personal and / or collective cartography of plenty different faces and purposes. Therefore in our paper, we aim to point out mapping processes and dynamics present in travel literature, or that it summons, allowing the detection of features and even the constants contained in travel writing poetic genre.